Agentic playful pre-service teachers: positionings from teacher-initiated playful teacher to community-shared playful teacher - Melasalmi, Anitta; Siklander, Signe; Kangas, Marjaana; Hurme, Tarja-Riitta (Frontiers in Education, 2023)
Play and playfulness are understood as basic and vital elements of early childhood education (ECE), and together with playful pedagogies, they perform a central role in Finnish ECE. In multidisciplinary research, children's learning is generally understood through the inquiring process of play. However, playfulness, as opposed to play, has received relatively little scholarly attention, and educators' use of playfulness has received even less (Pinchover, 2017). Playfulness is a vital part of life for both adults and children. At the same time, teachers' behavior can influence the playfulness of a child; moreover, teachers' own playfulness is critical for establishing warm and secure relationships with children. As such, the aim of this research was to explore pre-service teachers' (PsTs') understanding of agentic playfulness, particularly in the ECE context. Study participants included 159 PsTs; study data were gathered from PsTs' written reflections regarding the use of playfulness in their future work. The results of qualitative analyses showed that the PsTs' agentic playfulness mirrored a relational and tensious space consisting of three domains: teacherinitiated agentic playfulness, child-centered agentic playfulness, and community-shared agentic playfulness. Each domain revealed dimensions of the nature of PsTs' mindset and the orientation of their agentic playfulness. The results are discussed in relation to pedagogization of play, relational pedagogy community of learners, and teacher education supporting and developing future ECE teachers' agentic playfulness.